Relationship between Phytoplankton Abundance and Water Quality Parameters in the SeagrassEcosystem in the Coastof Nirwana Beach, Padang, Sumatera Barat Province - Septiyawati '; Adriman '; Eni Sumiarsih (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Nirwana Beach in West Sumatera,is commonly used for tourism, fisheries and domestic activities that potential in affecting the water quality. This research aims to determine the relationship between water quality parameters and the phytoplankton abundance in the seagrassecosystem in that beach. Samplings were conducted in September 2016, 3 times, once/ week in 3 stations.          Results shown thatthere were 30 phytoplankton types, consists of five classes, namely Bacillariophyceae (17 spesies), Chlorophyceae (6 spesies), Cyanophyceae(5 spesies), Dinophyceae (1 species) and Xantophyceae (1 species). The abundance of phytoplankton ranged from 12,292 to 23,646 cells/L. the H' was 4.017 to 4.425; C was 0.057 to 0.088 and E was 0.819 to 0.902. Water quality parameters value indicates that it supports the life of phytoplankton. There is a very strong relationship (95%) between the abundance of phytoplankton and water quality parameters. Keywords: NirwanaBeach, Phytoplankton Abundance, Seagrass Ecosystem, WaterQualityParameters